Troglitazone Impedes the Oligomerization of Sodium Taurocholate Cotransporting Polypeptide and Entry of Hepatitis B Virus Into Hepatocytes - Fukano, Kento; Tsukuda, Senko; Oshima, Mizuki; Suzuki, Ryosuke; Aizaki, Hideki; Ohki, Mio; Park, Sam-Yong; Muramatsu, Masamichi; Wakita, Takaji; Sureau, Camille; Ogasawara, Yuki; Watashi, Koichi (Frontiers in Microbiology, 2019)
Current anti-hepatitis B virus (HBV) agents, which include nucleos(t)ide analogs and interferons, can significantly suppress HBV infection. However, there are limitations in the therapeutic efficacy of these agents, indicating the need to develop anti-HBV agents with different modes of action. In this study, through a functional cell-based chemical screening, we found that a thiazolidinedione, troglitazone, inhibits HBV infection independently of the compound's ligand activity for peroxisome proliferator-activated receptor γ (PPARγ). Analog analysis suggested chemical moiety required for the anti-HBV activity and identified ciglitazone as an analog having higher anti-HBV potency. Whereas, most of the reported HBV entry inhibitors target viral attachment to the cell surface, troglitazone blocked a process subsequent to viral attachment, i.e., internalization of HBV preS1 and its receptor, sodium taurocholate cotransporting polypeptide (NTCP). We also found that NTCP was markedly oligomerized in the presence of HBV preS1, but such NTCP oligomerization was abrogated by treatment with troglitazone, but not with pioglitazone, correlating with inhibition activity to viral internalization. Also, competitive peptides that blocked NTCP oligomerization impeded viral internalization and infection. This work represents the first report identifying small molecules and peptides that specifically inhibit the internalization of HBV. This study is also significant in proposing a possible role for NTCP oligomerization in viral entry, which will shed a light on a new aspect of the cellular mechanisms regulating HBV infection.